Increased expression of OLFM4 and lysozyme during necrotizing enterocolitis in neonates: an observational research study - Diez, Sonja; Renner, Marcus; Bahlinger, Veronika; Hartmann, Arndt; Besendörfer, Manuel; Müller, Hannah (BMC pediatrics, 2022)
In neonatal patients with necrotizing enterocolitis (NEC) the inflammatory response is mediated by a plurality of different proteins. The proteins olfactomedin 4 (OLFM4) and lysozyme (LYZ) are part of the intestinal mucosal defense and especially OLFM4 has rarely been evaluated in neonatal gastrointestinal diseases. The aim of this study was to analyze whether expression levels of both proteins of innate immunity, OLFM4 and lysozyme, were increased during NEC in neonates.
Gesehen am 06.07.2022